Penulisan Sejarah Rekonsiliatif: Refleksi Pendampingan Penulisan Tambo Nagari Pakan Rabaa Timur - Muhammad Nasir (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
The process of writing Tambo Nagari Pakan Rabaa Timur, which contains information on the history of the nagari, is a reflection of a complex society, including episodes of the journey of conflict that have garnered their memories for some time. In an effort to reconcile the turbulent past, the model of reconciling historical writing can be used as an alternative approach. This paper is a reflection model of the implementation of participatory activities in the preparation of Tambo Nagari Pakan Rabaa Timur, a work of local history using focus group discussion methods, content analysis and in-depth interviews. The results show that community involvement in the drafting process has succeeded in presenting local perspectives by using balanced narratives, inclusive approaches, and in-depth understanding sourced from Minangkabau local wisdom. The model of reconciling historical writing, as seen in Tambo Nagari Pakan Rabaa Timur, can be considered as a development of contemporary Minangkabau historiography.